2013
DOI: 10.1007/s10439-012-0733-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Biaxial Mechanical Behavior of Porcine Aorta under Gradual Elastin Degradation

Abstract: Arteries are composed of multiple constituents that endow the wall with proper structure and function. Many vascular diseases are associated with prominent mechanical and biological alterations in the wall constituents. In this study, planar biaxial tensile test data of elastase-treated porcine aortic tissue (Chow et al. 2012) is re-examined to characterize the altered mechanical behavior at multiple stages of digestion through constitutive modeling. Exponential-based as well as recruitment-based strain energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 62 publications
5
43
1
Order By: Relevance
“…Gundiah, et al reported decreases in k 2 in collagenase samples compared with controls, as here, but with an accompanying increase in k 1 , the latter not seen here [18]. Zeinali-Davarani, et al performed gradual elastase digestion of porcine aorta [19]. They found that partial digestion led to a decrease in k 2 compared with control samples, as seen here.…”
Section: Goh Parameters K 1 and Ksupporting
confidence: 75%
See 2 more Smart Citations
“…Gundiah, et al reported decreases in k 2 in collagenase samples compared with controls, as here, but with an accompanying increase in k 1 , the latter not seen here [18]. Zeinali-Davarani, et al performed gradual elastase digestion of porcine aorta [19]. They found that partial digestion led to a decrease in k 2 compared with control samples, as seen here.…”
Section: Goh Parameters K 1 and Ksupporting
confidence: 75%
“…Zeinali-Davarani et al reported an increase in θ compared to control samples for partial digestion, whereas a decrease is reported here [19]. However, they also found that θ reduces to a similar angle as the control with further digestion.…”
Section: Fibre Angle θcontrasting
confidence: 51%
See 1 more Smart Citation
“…The degree of tone, and therefore, extent of PEC compression, was found to represent 12% to 20% of the nitroprusside-relaxed vessel circumference, depending on the degree of VSM destruction. Other studies support the view that elastic fibers are normally under tension and collagen fibers are under compression, at least in elastic arteries, because elastin degradation with elastase causes increases in tissue length by up to 30% concomitant with collagen fiber straightening (72,534). These critical studies underscore the notion that the SEC load cannot be assumed to be zero in a fully relaxed VSM under zero external load.…”
Section: Ecmmentioning
confidence: 79%
“…Future work must focus on additional microstructural characterization, such as collagen fibre orientation [45], fibre recruitment [46], cross-link density [47] and overall organization within the three-dimensional wall under physiologic loading conditions. Previous work has shown that chemical degradation of elastic fibres [48,49] or alterations to the elastic fibres through the loss of fibulin-5 expression [13,14], reduced levels of fibrillin-1 [50] or mutations in the fibrillin-1 gene [51] affect collagen fibre orientation and recruitment. Understanding how collagen fibre structure and mechanics compensate for defective elastic fibres to meet the design constraints of the maturing aortic wall may help to manipulate this process in disease treatments and duplicate the process in tissue engineering.…”
Section: Predictions Of the Constitutive Modelmentioning
confidence: 99%